Kajian Wawasan Al-Qur’an Tentang Etos Kerja Dalam Perspektif Islam - Fahruddin; Hasyim Hadadde; Hamka Ilyas (CV. SINAR HOWUHOWU, 2026)
This study examines the Quranic perspective on work ethic as a key to productivity and well-being within an Islamic framework. Employing a thematic exegesis (*maudhu’i*) approach, the article gathers and analyzes Quranic verses concerning work, trust (*amanah*), professionalism (*itqān*), and the balance between worldly life and the Hereafter. The findings indicate that the Islamic work ethic positions work as an act of worship and a trust, rather than merely an economic activity. Work performed with sincere intention, honesty, and high professionalism serves as a means to attain blessings and both personal and social well-being. In the modern era, Quranic work ethic values ​​remain relevant as a moral and spiritual compass for Muslim workers navigating the currents of globalization, the industrial revolution, and dynamic social changes. This research contributes to the understanding that strengthening human resources based on faith and piety, alongside the application of an Islamic work ethic, serves as a vital foundation for enhancing national productivity and achieving sustainable well-being.